The Significance of the Competence of the Subjects of the Educational Process in the Quality of Education - Saodat Abdurashidovna Toshtemirova; Dilnur Ravubkizi Bozorova (Zien Journals, 2023)
In this article, the concept of competence and its philosophical-pedagogical analysis, the opinions of scientists on this concept are presented, the basic competencies are analyzed, the importance of the competence of subjects (teachers and students) in improving the quality of education is highlighted, and the main factors in the educational system based on the competency approach are mentioned.
Keywords: competence; professional qualification